Babylonian Letters from the Kuyunjik Collection: Seventh Century Uruk in New Epistolary Evidence. Ph.D. Dissertation - Arnold, В. Т. (1985)
Referees: D. Weisberg, S. Greengus. - Order No. DA8519698. Cf. DissAbstr 46/07 (January 1986). 2043-A